1993
DOI: 10.2307/3431506
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Genotoxic Exposure in Uranium Miners

Abstract: Recent data from deep uranium mines in Czechoslovakia indicated that in addition to radon daughter products, miners are also exposed to chemical mutagens. Mycotordns were identified as a possible source of mutagenicity present in the mines. Various methods of biomonitoring were used to eaamine three groups of miners from different uranium mies. Cytogenetic analysis of peripheral lymphocytes, unscheduled DNA synthesis (UDS) in lymphocytes, and lipid peroxidation (LPO) in both plasma and lymphocytes were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…CIT has been mostly identified primarily in moldy rice and corn in parts of Asia and South America (Rosa et al, ; Almeida et al, ). CIT has also been isolated from uranium mines and miners' throats (Sram et al, ). It has been shown that the contamination levels of CIT in grains were between 4.9 and 33.2 µg/kg in the target areas of China (Hou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…CIT has been mostly identified primarily in moldy rice and corn in parts of Asia and South America (Rosa et al, ; Almeida et al, ). CIT has also been isolated from uranium mines and miners' throats (Sram et al, ). It has been shown that the contamination levels of CIT in grains were between 4.9 and 33.2 µg/kg in the target areas of China (Hou et al, ).…”
Section: Introductionmentioning
confidence: 99%